The Oral Microbiome in Health and Its Implication in Oral and Systemic Diseases - Sampaio-Maia, B; Caldas, I M; Pereira, M L; Pérez-Mongiovi, D; Araujo, R (Advances in applied microbiology, 2016)
The oral microbiome can alter the balance between health and disease, locally and systemically. Within the oral cavity, bacteria, archaea, fungi, protozoa, and viruses may all be found, each having a particular role, but strongly interacting with each other and with the host, in sickness or in health. A description on how colonization occurs and how the oral microbiome dynamically evolves throughout the host's life is given. In this chapter the authors also address oral and nonoral conditions in which oral microorganisms may play a role in the etiology and progression, presenting the up-to-date knowledge on oral dysbiosis as well as the known underlying pathophysiologic mechanisms involving oral microorganisms in each condition. In oral pathology, oral microorganisms are associated with several diseases, namely dental caries, periodontal diseases, endodontic infections, and also oral cancer. In systemic diseases, nonoral infections, adverse pregnancy outcomes, cardiovascular diseases, and diabetes are among the most prevalent pathologies linked with oral cavity microorganisms. The knowledge on how colonization occurs, how oral microbiome coevolves with the host, and how oral microorganisms interact with each other may be a key factor to understand diseases etiology and progression.